A review of experimental and theoretical fracture characterization of bi-material bonded joints. (1st February 2021) - Wang, Wandong; De Freitas, Sofia Teixeira; Poulis, Johannes A.; Zarouchas, Dimitrios
Abstract: High performance structures require the use of different materials to meet their demanding requirements. Especially fibre reinforced polymer composites are nowadays often bonded to metals in order to take the most advantage of the materials properties and to minimize their disadvantages. However, the interface in such bi-material assemblies often represents the weakest point and thus has to be carefully addressed to ensure structural integrity. This review paper presents an overview of the research on bi-material interface crack problems over the past 30 years. Three categories of the research are discussed: mechanical testing, crack driving force and mode partitioning. The literature reveals that the key element to the fracture analysis of the bi-material interface crack is how to perform the mode partitioning. The proposed theories for mode partitioning by many researchers are meaningful yet underdeveloped and need further experimental validation.